116 Polyclonal antibody preparations from avian origin improves growth performance of beef cattle during the first fourteen days of the backgrounding phase. (29th July 2019) - da Silva, Gleise Medeiros; Podversich, Federico; Schulmeister, Tessa; Luna, Ana C G; Barreneche, Gonzalo; DiLorenzo, Nicolas
Abstract: This study aimed to evaluate the effects of feeding avian-derived polyclonal antibody preparation (PAP; CAMAS, Inc.) against Streptococcus bovis, Fusobacterium necrophorum, and lipopolysaccharides (40, 35, and 25% of the preparation, respectively) on growth performance of beef cattle during the backgrounding phase. From d 0 to 56, Angus crossbreed heifers (n = 80; 360 ± 60 kg of BW; 470 ± 26 d of age) and steers (n = 20; 386 ± 65 kg of BW; 465 ± 30 d of age) were blocked by BW and randomly assigned to 1 of 16 concrete-floored pens (108 m 2 ), equipped with 2 GrowSafe (GrowSafe Systems Ltd., Airdrie, Alberta, Canada) feed bunks each. Animals received a common ad libitum diet (76% TDN, 15.9% CP, DM basis) with the addition of 1 (PAP1), 3 (PAP3), or 0 g (CON) of PAP per d. Feed intake was recorded daily and BW were obtained on d -1, 0, 14, 28, 42, 55, and 56, to assess changes in BW, ADG, DMI, and G:F. Based upon orthogonal contrasts (CON vs. PAP1, and PAP1 vs. PAP3), BW and ADG on d 14, and DMI from 0 to 28, and 0 to 42 were greater for PAP1 vs. CON (P ≤ 0.03), whereas PAP3 animals were intermediate (P ≥ 0.20). No differences in final BW, DMI, and ADG from d 0 to 56 were detected among treatments (P ≥ 0.22). In conclusion, feeding 1g of polyclonal antibody preparations against Streptococcus bovis, Fusobacterium necrophorum, and lipopolysaccharides in a backgrounding diet, improved growth performance in the first 14 d of feeding suggesting that feeding these PAP for longer than 14 d may not be necessary. The effects on subsequent feedlot performance when using PAP should be evaluated in future studies